OPTIMASI FORMULA SUSPENSI SIPROFLOKSASIN DENGAN KOMBINASI PULVIS GUMMI ARABICI (PGA) DAN CARBOPOL 934 MENGGUNAKAN METODE DESAIN FAKTORIAL - ., Sainah (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2013)
ABSTRACTCiprofloxacin is an antibiotic that has low solubility in water and formed intosuspension in order to produce stable product in liquid form. This research aims tooptimize the proportion of a mixture suspending agent in order to produce optimumphysical properties. Optimize suspension physical properties used factorial designmethod with Design Expert software version 8.0.7.1 trial. Pulvis Gummi Arabici (PGA)and Carbopol 934 as independent variable meanwhile viscosity, sedimentation volumeand redispersibility as dependent variable. Based on that method, obtained four formula(formula A, B, C, and D) and physical properties were measured. Analytical of the resultsobtained from the equations and graphs for each response, by which optimum formulacan be determined. The optimum formula based on factorial design method was FormulaA (Carbopol 934 and PGA low concentration) with value of desirability 0,684 and showlow viscosity, particles rapidly settle but easy redispersibility. Analytical statistic ofphysical properties in optimum formula and prediction show insignificance difference (pvalue> 0,05). The antibacterial activity in optimum formula and positive control(ciprofloxacin) show insignificance difference (p-value > 0,05) which mean ciprofloxacinstill has antibacterial activity in suspension form. Key Words : ciprofloxacin, suspension, PGA, carbopol 934, Factorial Design